PASINRLIKAS A SINTAS EXISTENCE SYNRILLIC MAKASSAR - Haslinda Haslinda; Ratnawati Ratnawati (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
This research aims to study pasinrilik as a survivor of the existence of sinrilik Makassar. The method used in this research is library research with the stages of using literature, reading combined with in-depth analysis to reach the formulation of ideas.The results of this writing analysis can be concluded that sinrilik is a type of oral literature that has undergone a process of overwriting. This type of literature is spoken using a rhythmic tone of voice. In certain performances, sinrilik's narrative is accompanied by a musical instrument called kesok-kesok. While pasinrilik refers to people who say sinrilik. The existence of pasinrilik can be traced in history, first introduced by the 10th King of Gowa led by I Manriagau Daeng Bonto Lakiung Tunipallangga Ulaweng (1510-1546).The essence of being a pasinrilik survivor has an important position, namely the position of pasinrilik as; (1) messenger; (2) become an instrument of customs; (3) become a storyteller; (4) Makassar language preservers; (5) as an artist; and (6) as a writer. To be a pasinrilik, you have to master narration and cyrillic recitation, it is very important to know the substance of the storyline and recitation related to how to tell it. There are several postnatal survival challenges, including; (1) pasinrilik at an advanced age and the interest of the younger generation is small; (2) urbanization of the younger generation; (3) local government policies; (4) literacy; and (5) millennial culture shock.